Rely-X unicem self-adhesive universal resin cement - Saleh Zidan; Syed Wali Peeran; Karthikeyan Ramalingam (Wolters Kluwer Medknow Publications, 2015)
There is an expansive usage of adhesives in all branches of dentistry. Newer adhesives can be more beneficial to the patients. This review attempts to highlight the important features of adhesive cements in general and emphasize the applications of Rely-X Unicem cement.